(untitled) (Sociologisk Forskning, 2019)
Swedish labour market policy faces major challenges . Sweden has a labour deficit and a very low unemployment rate at the same time as unemployment is high among young people and immigrants . Unemployed in Sweden with high thresholds to enter the labour market are referred to the local labour market policy where the municipalities co-operates, competes and negotiates with the Public Employment Service (PES) . The purpose of this study is to understand the organizational boundaries between PES and the municipalities and how these boundaries affects the local labour market policy in eleven municipalities . We have carried out semi-structured group interviews with managers . The boundaries between PES and the municipalities are vague and require negotiations regarding resources such as the unemployed, different forms of activities offered to the unemployed and economic resources . Clearer boundaries would generate condi- tions that offer unemployed people a strategic organization of the local labour market policy with enhanced co-operation and adaptation to common goals instead of competition and large amount of time spent on negotiating.